Produk Hukum Pemerintah Daerah - Abdi Syahputra Ritonga; Farhan Azhari Harahap; M. Rabitha Lufthansa (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This research discusses legal products produced by regional governments in the context of implementing regional autonomy. Regional legal products include various types of regulations such as regional regulations (perda), governor regulations, and regent/mayor regulations which have an important position in local government governance. This research aims to analyze the creation process, substance and legal impact of regional legal products on society and regional government. The method used in this research is a normative juridical approach using qualitative analysis of regulations issued by regional governments. The research results show that although regional legal products have a significant role in encouraging regional progress, there are a number of challenges related to synchronization between regional regulations and higher-level legislation. Apart from that, the effectiveness of regional legal products in responding to community needs still faces obstacles in implementation in the field. This research suggests the need to strengthen the capacity of regional government officials in preparing and supervising legal products, as well as increasing synergy between central and regional governments in order to realize more effective regional autonomy.